2020
DOI: 10.1177/1082013220929152
|View full text |Cite
|
Sign up to set email alerts
|

Acerola fruit as a natural antioxidant ingredient for gluten-free bread: An approach to improve bread quality

Abstract: In this study, we evaluated the effect of enrichment of bread using acerola fruit powder on the physical, sensorial and antioxidant properties of gluten-free breads. We tested different proportions of acerola fruit powder (0–5% w/w) in rice flour. According to the results, loaf volume increased from 423.33 cm3 to 571.67 cm with increasing amount of acerola fruit powder cm3 with increasing amount of acerola fruit powder (from 0 to 5% w/w). Acerola fruit powder improved the structural parameters of the crumb by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…Similarly, Bourekoua et al. (2021) found that, the replacement of rice flour with acerola fruit up to 3% in bread did not affect the sensory attributes adversely. As one of the most important parameters in developing a food product is the consumer acceptance, the sensorial evaluation of this study was one of the criteria for determining the best breadstick formulation.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, Bourekoua et al. (2021) found that, the replacement of rice flour with acerola fruit up to 3% in bread did not affect the sensory attributes adversely. As one of the most important parameters in developing a food product is the consumer acceptance, the sensorial evaluation of this study was one of the criteria for determining the best breadstick formulation.…”
Section: Resultsmentioning
confidence: 88%
“…In general, breads formulated with gluten-free raw materials have low nutritional properties, poor taste, and are of inferior quality. In the absence of gluten, dough presents poor rheological properties (viscoelasticity) and is unable to develop a protein network, affecting the final quality of gluten-free bread [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Stworzono ryżowe pieczywo bezglutenowe wzbogacane proszkiem z owoców aceroli o szczególnie cennych właściwościach fizyko-sensorycznych i przeciwutleniających. Wykazano, że częściowe zastąpienie mąki ryżowej (w ilości do 3% masy mąki niezbędnej do wytworzenia pieczywa) proszkiem z owoców aceroli przyczynia się do zmniejszenia przeżuwalności (wielokrotności żucia potrzebnego do rozdrobnienia pokarmu) przy jednocześnie zwiększonej sprężystości otrzymanego produktu (Bourekoua i Gawlik-Dziki, 2021). Ponadto wykazano, że proszek z owoców aceroli jest w stanie poprawić również parametry strukturalne pieczywa, m.in.…”
Section: Acerola W Produkcji Wzbogacanych Produktów Piekarniczychunclassified
“…zwiększając wielkość i udział powierzchniowy komórek miękiszu, co ostatecznie umożliwia wytworzenie pieczywa (bochenka chleba), którego objętość jest prawie o 26% większa względem pieczywa ryżowego bez dodatku owoców aceroli. Stwierdzono, że dodatek sproszkowanego owocu aceroli zwiększa również całkowitą zawartość związków polifenolowych oraz ogólną aktywność przeciwutleniającą pieczywa (Bourekoua i Gawlik-Dziki, 2021).…”
Section: Acerola W Produkcji Wzbogacanych Produktów Piekarniczychunclassified
See 1 more Smart Citation